The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12033-015-9865-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering and Regenerative Medicine in Iran: Current State of Research and Future Outlook

Abstract: During two decades ago, Iran has exhibited remarkable increase in scientific publication in different aspects including tissue engineering and regenerative medicine (TERM). The field of TERM in Iran dates comes back to the early part of the 1990 and the advent of stem cell researches. Nowadays, Iran is one of the privileged countries in stem cell therapy in the Middle East. The next major milestone in TERM was application and fabrication of scaffolds for tissue engineering in the early 2000s with a focus on en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 162 publications
0
6
0
Order By: Relevance
“…A rare example of research with an impact found in the literature was from Royan Institute, an Iranian stem cell research center approved by MOHME in 1998, where research is translated into medical services. It was reported that the center provides stem cell therapy for skin and cartilage disorders [ 145 ]. Finally, in 2003, it was reported that 13 national research studies had led to an improvement or change in the health system, while about 20 national guidelines for use in the health system had been reformulated based on the outcomes of locally conducted research (references to specific studies were not given)[ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…A rare example of research with an impact found in the literature was from Royan Institute, an Iranian stem cell research center approved by MOHME in 1998, where research is translated into medical services. It was reported that the center provides stem cell therapy for skin and cartilage disorders [ 145 ]. Finally, in 2003, it was reported that 13 national research studies had led to an improvement or change in the health system, while about 20 national guidelines for use in the health system had been reformulated based on the outcomes of locally conducted research (references to specific studies were not given)[ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the traditional porous material preparation process, the biggest advantage of 3D printing technology is that it can accurately control the structure of the bioceramic scaffold (including the size and shape of the internal pores, and the overall shape of the scaffold) from micro to macro scale. This feature enables 3D printing technology to design tissue engineering scaffolds to repair tissue defects for patients according to actual needs, to achieve precision medicine [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The most used 3D printing techniques are briefly described in Table 3 .…”
Section: Bioceramic 3d Printing Overviewmentioning
confidence: 99%
“…For example, the structural elements of the scaffold printed by DIW technology is a cylindrical pillar with a certain diameter, which makes the printing accuracy of DIW technology lower than that of SLA printing technology. For some complex structures, DIW technology requires additional support to assist in printing; during the printing process, the support may be dented and deformed [ 9 , 10 , 11 , 12 ]. These disadvantages limit the application of DIW technology, making it unsuitable for the preparation of higher precision materials.…”
Section: Bioceramic 3d Printing Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However because their biodegradation behaviour is unpredictable they are not a good candidate for controlled delivery of Simvastatin. 1,4,105,110,111 Hybrid materials that are made by combination of synthetic and natural materials can be used to produce bone scaffolds that have good bioactivity and drug delivery properties. 4 Inorganic materials such as hydroxyapatite (HA), three calcium phosphate (TCP) and bio glasses are often combined with organic and synthetic materials in order to increase the biomimetic properties of bone scaffolds.…”
Section: Biomaterials Used To Locally Deliver Simvastatinmentioning
confidence: 99%